Germany : Staff Report for the 2015 Article IV Consultation. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2015)
This 2015 Article IV Consultation highlights that the ongoing upturn in Germany is benefiting from the euro depreciation and lower energy prices, and is underpinned by a healthy fiscal position and sound corporate and household balance sheets. Employment growth has been robust, supported by strong immigration. The unemployment rate hit an additional post-reunification low at 4.7 percent. The oil price drop brought inflation temporarily close to zero, which has contributed to lift real wage growth to a 20-year high. The current moderate growth momentum is expected to continue as robust real wages buoy private consumption and euro depreciation buttresses exports, opening the way for a recovery in machinery and equipment investment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet